Semaphorin Regulation by the Chromatin Remodeler CHD7: An Emerging Genetic Interaction Shaping Neural Cells and Neural Crest in Development and Cancer - Lettieri, Antonella; Oleari, Roberto; Paganoni, Alyssa J. J.; Gervasini, Cristina; Massa, Valentina; Fantin, Alessandro; Cariboni, Anna (Frontiers in Cell and Developmental Biology, 2021)
CHD7 is a chromatin remodeller protein that controls gene expression via the formation of multi-protein complexes with specific transcription factors. During development, CHD7 controls several differentiation programs, mainly by acting on neural progenitors and neural crest (NC) cells. Thus, its roles range from the central nervous system to the peripheral nervous system and the organs colonised by NC cells, including the heart. Accordingly, mutated CHD7 is linked to CHARGE syndrome, which is characterised by several neuronal dysfunctions and by malformations of NC-derived/populated organs. Altered CHD7 has also been associated with different neoplastic transformations. Interestingly, recent evidence revealed that semaphorins, a class of molecules involved in developmental and pathological processes similar to those controlled by CHD7, are regulated by CHD7 in a context-specific manner. In this paper, we will review the recent insights that support the existence of genetic interactions between these pathways, both during developmental processes and cancer progression.